The function `y = x/(sqrt(x^2+1))` only has horizontal asymptotes.

As x tends to inf.

`lim_(x->oo)x/sqrt(x^2+1)`

as x tend to inf., 1/x tends to 0

=> `lim_(1/x->0)x/(x*sqrt(1+1/x^2))`

=> `lim_(1/x->0)1/sqrt(1+1/x^2)`

substitute 1/x = 0

=> 1

As x tends to -inf.

`lim_(x->-oo)x/sqrt(x^2+1)`

=> `lim_(x->oo) (-x)/sqrt((-x)^2+1)`

=> `lim_(x->oo)(-x)/sqrt(x^2+1)`

As x tends to inf.,...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The function `y = x/(sqrt(x^2+1))` only has horizontal asymptotes.

As x tends to inf.

`lim_(x->oo)x/sqrt(x^2+1)`

as x tend to inf., 1/x tends to 0

=> `lim_(1/x->0)x/(x*sqrt(1+1/x^2))`

=> `lim_(1/x->0)1/sqrt(1+1/x^2)`

substitute 1/x = 0

=> 1

As x tends to -inf.

`lim_(x->-oo)x/sqrt(x^2+1)`

=> `lim_(x->oo) (-x)/sqrt((-x)^2+1)`

=> `lim_(x->oo)(-x)/sqrt(x^2+1)`

As x tends to inf., 1/x tends to 0

=> `lim_(1/x->0)(-x)/(x*sqrt(1+1/x^2))`

=> `lim_(1/x->0)(-1)/sqrt(1+1/x^2)`

substitute 1/x = 0

=> -1

**The asymptotes are y = 1 and y = -1**